The Association Between Sedentary Screen Time, Non-screen-based Sedentary Time, and Overweight in Chinese Preschool Children: A Cross-Sectional Study - Rui Hu; Hui Zheng; Congchao Lu; Congchao Lu (Frontiers Media S.A., 2021)
Introduction: Less is known about the effects of the different domains of sedentary behaviors on healthy weight in young children. This cross-sectional study examined the association between sedentary screen time (SST), non-screen-based sedentary time (NSST), and overweight (and obesity) in Chinese preschoolers.Methods: Data were collected from the Physical Activity and Health in Tianjin Chinese Children study (PATH-CC), involving healthy children 3-6 years old and their families. Children's overweight status was classified according to the international (IOTF) childhood BMI cut-offs. SST and NSST were reported in minutes/day by parents using the leisure-time sedentary behaviors questionnaire. Logistic regression models adjusted by sex, age, socioeconomic status, outdoor play, and sleep duration were used.Results: In a total of 971 children (55.4% boys), 11.8% were overweight. Generally, children spent 1 h/day in SST and 1 h/day in NSST. Multiple models showed that children who spent more time in SST were more likely to be overweight [OR and 95% CI: 1.22 (1.03-1.45)]. No correlation between time spent on NSST and children with overweight was found (P > 0.05).Conclusions: This study indicated that children who spent more time in SST were more likely to be overweight, but a null correlation between NSST and overweight was found. Longitudinal studies designed to identify associations between exposures to screen media and changes in metabolic parameters during a child's early years are needed.